Analysis of the Influence of Capital Structure and Work Effectiveness Employees on Bumdes Financial Performance: Analysis of the Influence of Capital Structure and Work Effectiveness Employees on Bumdes Financial Performance - Indra Nugraha, Ramlan; Z. Soeratin , Harry; Gulo, Nurdelima (Jurnal Administrasi Publik dan Bisnis, 2024)
This research aims to determine the influence of capital structure and employee work effectiveness on the financial performance of BUMDES. The sample in this study consisted of 20 respondents. The data collection technique used an 18-item questionnaire. The questionnaire was declared reliable with 0.714 for the capital structure variable, 0.516 for the employee work effectiveness variable and 0.544 for the BUMDES financial performance variable. The data that was collected was analyzed using descriptive and inferential statistics. The data analysis technique used is the multiple linear regression test, R determination and to test the hypothesis the t test is used. This test is carried out to measure the influence partially, while to measure the influence simultaneously the F test is used. The results of the study show that the employee work effectiveness variable (X2 ) has a positive and significant effect on the financial performance of BUMDES (Y). In the F test, the value Fcount = 8.957 is obtained, then a comparison is made between Fcount = 8.957 > Ftable = 3.59 with a significance value of 0.000 < 0.05, which means the hypothesis is accepted. So it can be concluded that the capital structure variables (X1) and employee work effectiveness (X2) have a positive and significant effect on the financial performance of BUMDES (Y). Based on the processing results, the R Square figure is 81.30 or 81.30%. These results indicate that the percentage contribution of the influence of independent variables, namely capital structure and employee work effectiveness on BUMDES financial performance is 18.70%. Meanwhile, the remaining 0.187 or 18.70% is influenced by other variables not studied in this research.